SISTEM PAKAR DIAGNOSIS PENYAKIT PADA KUCING DENGAN METODE FORWARD CHAINING PADA KLINIK HEWAN MITRA SATWA - -, Pariyadi; -, Afrizal; Novraniar, Ghitra; Adhiatma, Novri (LP2M Universitas Nurdin Hamzah, 2023)
Cats are one type of animal that is widely kept and popular as a favorite pet among the public. Cat health is very important, this is inseparable from the role of veterinary hospital clinics which are needed to perform medical actions on pets. The purpose of the study is to build an Expert System for Diagnosing Disease in Cats with the Forward Chaining Method at Mitra Satwa Jambi Clinic which is a system that can replace the temporary role of experts in identifying diseases in cats quickly and accurately, and Provide solutions to cat lovers to provide first treatment to cats. The results of the analysis and evaluation show that the expert system uses Forward Chaining in this approach using reasoning in the expert system which starts based on the information that provided to users in the form of existing facts.